Notes on the genesis, reception and intertextual relationships of ignorance in Vallejo. "Los Heraldos Negros" and its influence on Jaime Gil de Biedma's "Los aparecidos" - Armisén, Antonio (Tropelías: Review of Literary Theory and Comparative Literature, 1995)
This paper confirms the great significance of the relationship between Vallejo's poetry and that of Fray Luis de León and San Juan de la Cruz. The Peruvian poet's early upbringing as a Christian, his knowledge of the Bible, his work as a reader and as a poet interested in the Spanish golden age poetry, reappraised in the light of his ideological evolution, the problem of ignorance and the modern myth of the death of God, all make for a better understanding of his main texts. His personal vision of an increasingly secularized world reached a limit. His personal new pact, with its implications of solidarity, acquired the formal reality of writing and constituted a renewing poetic sacralization. This article attempts to trace back the most important and radical features of formal deconstruction in "Intensidad y altura" already apparent in earlier poems such as "La cena miserable", "Dios" and, particularly, "Hojas de ébano". Other matters that come in for critical attention are: a revision of the opinions of some Vallejo scholars, the extent to which the model of Job operates in his poetic language and the influence of the Peruvian poet on Gil de Biedma's social and realist poetry.
Keywords: César Vallejo; Jaime Gil de Biedma